CAGE17-1-Leg 2 cruise report - Rasmussen, Tine L.; Nielsen, Tove; Laier, Troels; Olsen, Bjørn R.; Iversen, Steinar; Sert, Mohamed; Jansson, Per; Serov, Pavel (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
From the afternoon of May 19th to the early morning of June 2nd 2017, CAGE-WP6 at the Department of Geology Uit, the Arctic University of Norway, arranged a scientific cruise aimed at investigating sediment cores and porewater, and water masses, at the western Svalbard margin, Fram Strait, East Greenland Ridge, and Storfjorden Trough, visiting methane seep sites off Vestnesa Ridge, and in Storfjorden Trough on R/V “Helmer Hanssen”. Investigated areas were (in order of visiting sites on the cruise): Prins Karls Forland (PKF) (overlap with ‘leg 1’ 17th to 19th of May – see Leg 1 report), southern Yermak Plateau, Vestnesa Ridge, East Greenland Ridge, Storfjorden Trough and Storfjorden. The scientific sampling was done within the framework of several ongoing projects at the Department of Geology, University of Tromsø: “CAGE – Centre for Arctic Gas Hydrate, Environment and Climate”-WP6: “Methane Release, Ocean Acidification and CO2”. Planned surveys north of Svalbard was abandoned due to extensive sea ice cover and the East Greenland Ridge was surveyed instead. Sea ice over outer Vestnesa prevented surveys there and Storfjorden trough was also completely covered, but the sea ice broke up towards the end of the cruise and thus could be surveyed during the very last part of the cruise. A total of 15 gravity cores (c. 60 m), and 20 CTD (conductivity-temperature-depth) casts were performed along the western Svalbard margin (Vestnesa and PKF and Yermak). Data were also collected at East Greenland Ridge and in Storfjorden Trough and Storfjorden, brine overflow was detected. The CTD casts and chirp- and multibeam lines from PKF May 17-19th are reported in the cruise report for Leg 1. Chirp profiles and multibeam lines were acquired during transits and in surveys (mapping of East Greenland Ridge, moraine systems and basins in Storfjorden Trough, active and inactive pockmarks at Vestnesa Ridge and over and to find potential core sites. The cruise may be known as: CAGE17_1_leg2